Financial Behavior in Yasinan Consumption - Suryaningtiyas Surya Pratiwi; Maretha Ika Prajawati (Jurnal Riset Akuntansi dan Keuangan, 2024)
This research was conducted to explore the meaning and determine the financial behavior of mothers in managing finances to carry out yasinan activities. This research uses a qualitative approach with a case study research type. In this study, data collection was carried out using three methods, namely interviews, observation, and documentation. The results of this study indicate that this yasinan activity is a hereditary activity that is carried out every week on Monday night and the place takes turns in the homes of the community. In this activity usually read yasin and istighosah, at the end of the event usually served consumption. The funds spent on yasinan consumption are quite large because in the past the consumption served was light food, now it has changed to heavy food. The considerations used to determine the consumption of yasinan are the consumption that is usually served by the mothers according to their development, price and type of food. In this case, mothers have good financial behavior by making wise financial decisions by planning in determining yasinan consumption.